New insights into thyroid dysfunction in patients with inactivating parathyroid hormone/parathyroid hormone-related protein signalling disorder (the hormonal and ultrasound aspects): One-centre preliminary results - Januś, Dominika; Roztoczyńska, Dorota; Janeczko, Magdalena; Starzyk, Jerzy B. (Frontiers in Endocrinology, 2022)
Objective This study aimed to present the spectrum of thyroid dysfunction, including hormonal and ultrasound aspects, in a cohort of paediatric and adult patients diagnosed with inactivating parathyroid hormone (PTH)/PTH-related protein signalling disorders 2 and 3 (iPPSD). Methods The medical records of 31 patients from 14 families diagnosed with iPPSD between 1980 and 2021 in a single tertiary unit were retrospectively analysed. Biochemical, hormonal, molecular, and ultrasonographic parameters were assessed. Results In total, 28 patients from 13 families were diagnosed with iPPSD2 (previously pseudohypoparathyroidism [PHP], PHP1A, and pseudo-PHP) at a mean age of 12.2 years (ranging from infancy to 48 years), and three patients from one family were diagnosed with iPPSD3 (PHP1B). Thyroid dysfunction was diagnosed in 21 of the 28 (75%) patients with iPPSD2. Neonatal screening detected congenital hypothyroidism (CH) in 4 of the 20 (20%) newborns. The spectrum of thyroid dysfunction included: CH, 3/21 (14.2%); CH and autoimmune thyroiditis with nodular goitre, 1/21 (4.8%); subclinical hypothyroidism, 10/21 (47.6%); subclinical hypothyroidism and nodular goitre, 1/21 (4.8%); primary hypothyroidism, 4/21 (19%); and autoimmune thyroiditis (Hashimoto and Graves’ disease), 2/21 (9.6%). Thyroid function was normal in 7 of the 28 (25%) patients with iPPSD2 and in all patients with iPPSD3. Ultrasound evaluation of the thyroid gland revealed markedly inhomogeneous echogenicity and structure in all patients with thyroid dysfunction. Goitre was found in three patients. Conclusion The spectrum of thyroid dysfunction in iPPSD ranges from CH to autoimmune thyroiditis and nodular goitre. Ultrasonography of the thyroid gland may reveal an abnormal thyroid parenchyma.